Adiponectina como marcador subclínico no processo de aterosclerose: estudo longitudinal da saúde do adulto - Núbia Gabriela de Oliveira Brandão (2018)
The Longitudinal Study of Adult Health (ELSA - Brazil) is a multi-center, multidisciplinary cohort study aimed at investigating the incidence and risk factors for chronic diseases, including cardiovascular diseases, diabetes and obesity. It is known that adiponectin has a protective effect against atherosclerosis, presenting anti-atherogenic and anti-inflammatory properties, as well as modulating endothelial inflammatory response and vascular wall functions. So it is expected that the determination of adiponectin levels may have some importance in assessing subclinical factors in the context of chronicdegenerative diseases. Thus, serum adiponectin levels were determined in 529 participants from the ELSA - BRASIL, CI-MG. Associations among adiponectin levels, and sociodemographic and clinical data besides parameters of endothelial function, assessed by Peripheral Arterial Tonometry (BPA and PAT ratio), were investigated. These data were extracted from the ELSA - Brazil database, CI-MG, and serum levels of adiponectin were determined by ELISA. Reduced serum concentrations of adiponectin were observed in males, in a lower age group (35 to 44 years), blacks, in lower education and income, obese and dyslipidemic individuals, and those who consumed excess ethanol. Reduced levels of adiponectin were also observed in participants with HDLc <40 mg / dL compared to those with HDLc ≥ 40 mg / dL; with TG ≥ 150 mg / dL in relation to those with TG <150 mg / dL. Decreased levels of adiponectin were inversely related to BPA values and directly to the PAT ratio. In the multivariate logistic regression model, the variables male sex, statin use, insulin and HDLc showed a significant association with reduced levels of adiponectin. An analysis of the data as a whole allowed us to conclude that adiponectin levels varied according to the sociodemographic and clinical characteristics of the study participants; and that there was an association between reduced levels of adiponectin and risk factors predisposing to the metabolic syndrome, diabetes and dyslipidemia.